Dietary Practices and Nutrient Intake of Internally Displaced School Children in the West Region of Cameroon - Nwachan Mirabelle Boh; Ejoh Richard Aba; Chefu Burnice Lemfor (International Journal of Food Science)
Background and Aims. Poor diets and subsequent malnutrition are among the greatest current societal challenges triggering immense health and economic burden especially among populations that are forcibly displaced. It is indispensable to establish the dietary patterns of any population, especially in displaced populations, in order to develop and effectively implement interventions for the specific population. Methods. A cross-sectional study was conducted to assess dietary practices and nutrient adequacy of 307 internally displaced pupils aged between 5 and 15 years in the West Region of Cameroon. Pretested, structured interviewer questionnaires were used to collect data on the demographic and socioeconomic status of the children and their caregivers, the nutrition knowledge of caregivers, the dietary practices of the children, dietary diversity, their food sources, and coping strategies that were used during food shortage. SPSS version 23 was used to analyze the data. The dietary diversity of the children was assessed at the individual level using FAO method of assessing women’s dietary diversity score. Results. Out of the total 307 children, 148 (48.2%) were boys and 159 (51.8%) were girls. During food shortages, most of the mothers/caregivers (72%) used borrowing as the main auxiliary food source and others (28%) used food as payment for work or begging. A majority of the children (56%) usually ate only two times in a day. Most of the children were of unacceptable or low dietary diversity (66.2%). The most frequently consumed food group was cereals as it was eaten by 21% of the children, seven or more times per week; meanwhile, the least was animal products with only 3% of the children consuming it seven or more times weekly. Their diets were energy-deficient (1640.5±1.64 kcal) and unbalanced with daily inadequate protein (18.45±1.13 g), vitamin A (470.27±1.38 μg), and iron (4.02±0.08 mg) intake. The nutrition knowledge of the mothers/caregivers was poor as less than half (41%) of them had an acceptable nutrition knowledge. Conclusion. The high prevalence of poor dietary patterns and poor nutrition knowledge imposes the necessity of developing nutritional interventions and education strategies aimed at promoting healthy eating habits in the children.